2018
DOI: 10.1016/j.bbr.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-like behavior and other consequences of early life stress in mice with increased protein kinase A activity

Abstract: Anxiety disorders are associated with abnormalities in fear-learning and bias to threat; early life experiences are influential to the development of an anxiety-like phenotype in adulthood. We recently reported that adult mice (Prkar1a+/-) with haploinsufficiency for the main regulatory subunit of the protein kinase A (PKA) exhibit an anxiety-like phenotype associated with increased PKA activity in the amygdala. PKA is the main effector of cyclic adenosine mono-phosphate signaling, a key pathway involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Data from studies in mice also showed that decreased PKA, which is an effector molecule downstream of the cAMP regulatory unit (PKA reg), was associated with increased anxiety and higher PKA activity in the basolateral and central amygdala, as well as in the ventromedial hypothalamus (125,126). Consistently, increased PKA level from early life stress has been observed (117). Therefore, it remains unclear how PDE inhibitors could exert anxiolytic effects via the regulation of cAMP signaling.…”
Section: Differences In Molecular Signaling Pathways May Lead To Variable Trade-offs Between Phenotypesmentioning
confidence: 95%
See 1 more Smart Citation
“…Data from studies in mice also showed that decreased PKA, which is an effector molecule downstream of the cAMP regulatory unit (PKA reg), was associated with increased anxiety and higher PKA activity in the basolateral and central amygdala, as well as in the ventromedial hypothalamus (125,126). Consistently, increased PKA level from early life stress has been observed (117). Therefore, it remains unclear how PDE inhibitors could exert anxiolytic effects via the regulation of cAMP signaling.…”
Section: Differences In Molecular Signaling Pathways May Lead To Variable Trade-offs Between Phenotypesmentioning
confidence: 95%
“…As for mGluR inhibitors, PDE inhibitors have been linked to having anxiolytic effects, influencing neurogenesis, and mitigating the effects of corticosteroids (117)(118)(119)(120)(121). Evidently, the study of Beer et al (122) has shown how PDE inhibitors could reduce anxiety by elevating cAMP levels.…”
Section: Differences In Molecular Signaling Pathways May Lead To Variable Trade-offs Between Phenotypesmentioning
confidence: 99%
“…The activation of the TGR5-cAMP-protein kinase A (PKA) axis exerts an anti-inflammatory effect on microglia, which in turn promotes the phosphorylation of the target protein CREB. The cAMP/PKA/CREB signaling pathway is closely associated with anxiety (63)(64)(65)(66). The anti-anxiety effect of INT-777 is elicited through the activation of microglial cells, which modulate the TGR5/cAMP/PKA/CREB axis.…”
Section: Bile Acids Transmit Signals That Affect Anxiety Via the Dire...mentioning
confidence: 99%